L’invitation au partage : Salah Stétié entre semblances, ressemblances et convergences - Bruera, Franca (Elephant & Castle, 2020)
In this essay we intend to point out the recurrence of the concept of similarity in the poetic production of Lebanese French-speaking diplomat, poet and art critic, Salah Stétié. The search for analogies, similarities and convergences of ideas and cultures are the common thread of his poetry, which from 1973, when he published his first poetic collection, L’Eau froide gardée, extends to 2017, when he issued L’été du grand nuage. His search winds through a mosaic of cultures and traditions from East to West which are never completely mixed, but are wisely juxtaposed in terms of similarity and difference, in the perspective of a never invasive interpenetration of ideas, identities and knowledge.